FINANCIAL LITERACY AND INVESTMENT FOR THE FUTURE OF BERYL’S CHOCOLATE AND CONFECTIONERY AND BHD (SERI KEMBANGAN) EMPLOYEES - Debbi Chyntia Ovami; Sari Wulandari; Ita Mustika; Dea Laila Puspita; Kiki Amalia Harahap; Sheerad Sahid (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
This study aims to enhance financial literacy and investment knowledge among employees of Beryl’s Chocolate and Confectionery Sdn Bhd in Seri Kembangan. By adopting insights from international research and financial education programs implemented in developed countries such as the US, UK, and Australia, the company seeks to improve employees' financial decision-making, long-term savings, and investment strategies. This initiative includes structured training, interactive workshops, and workplace investment schemes, which are expected to enhance financial stability, reduce stress, and improve productivity and employee retention. Additionally, this research explores strengthening the competitiveness of Indonesian products through research conducted by the UMN Al-Washliyah team. By focusing on product innovation, digital transformation, and export readiness, the study provides SMEs with strategies to improve product quality, adopt sustainable production methods, and utilize e-commerce and financial technology to expand market reach. The Knowledge Transfer Program (KTP) plays a crucial role in bridging academia and industry, fostering collaboration among businesses, researchers, and government agencies to support sustainable economic growth. This research emphasizes the importance of financial literacy and investment knowledge in enhancing employee well-being while strengthening the global competitiveness of Indonesian products.